Kontribusi Sikap Sabar bagi Kesehatan Mental di Masa Pandemi Covid-19: Studi Kasus pada Mahasiswa Jurusan Tasawuf dan Psikoterapi Tingkat Akhir Angkatan 2017 - Asyifa Qurotul Ain Santika (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The Covid-19 pandemic has become something that has shocked the world, one of the impacts of this condition is the occurrence of mental health disorders, one of the things that can reduce mental health disorders is to be patient. The purpose of this study was to determine the contribution of patience to mental health during the Covid-19 pandemic. This research was conducted using descriptive qualitative research methods with library and interview techniques. The results and discussion of this research show that the Covid-19 pandemic is a disaster or a test that Allah has given and it is very influential on mental health, Allah also explains in the Qur'an that if a disaster or test is struck, one should be patient. The conclusion of this study is that patience has a major contribution to mental health, this makes them feel calmer, can accept the situation with grace, and think positively about the things they face. It is hoped that future researchers will use other methods in order to obtain more comprehensive results.